Avaliação sócio-ambiental da bubalinocultura e outros tensores ambientais nas unidades de paisagem do município de Viana-Ma, área de proteção ambiental da baixada maranhense - Santos, Ceália Cristine dos (2007)
The creation of buffalos in the state of Maranhão predominantly occupies the fields of Baixada, region situated to the north of the state characterized by the periodical flood that they are succeeded between two seasons: a drought and another rainy. The transformation of the region in area of environment protection increased the discussion concerning the socioenvironment impacts in the area. The city of Viana congregates the biggest flock of buffalos of Baixada, with extensive creation occupying great areas and causing to problems with farmers and fisheres, due the constant presence of animals in the natural pastures and the lakes and also due the existence of fences surround the field that difficult the access to the lake for the local fishing. This paper has the goal to evaluate the socio-environment impacts of the buffalo ranching and other environment tensors in the units of landscapes of Viana. The methodology consisted of interviews and application of questionnaires and use of digital images. From the mapping of units of landscapes and use (of the years of 1995 and 2004), growth was observed of farming in the Firm Land area. The results show, according to perception of the farmers and fishers, changes in the environment with the reduction of grassy as “capim boiador” (Paspalum repens) and “capim-marreca” (Paratheria prostrata) and of “macrofitas as gapéua” (Nymphoides indica) and “orelha de veado” (Pontederia sp). In the local fauna it was perceived reduction of population of “jaçanã” (Porphyrula martinica) and “marreca” (Dendrocygna viduata) and fish as “curimatá” (Prochilodus nigricans) and “traíra” (Hoplias malabaricus). This condition, according to interviewed they are environment effects of the buffalo ranching and other tensors as construction of barrages, deforestation, forest fires and population increase. The interviewed had informed that the conflicts generated for the existing buffalos although they had attenuated due the reduction of the flocks. The research evidenced that the changes socio- environment they can be reduced in next decades if the sustentation of ecosystems will be understood. The city of Viana, ahead of the diversification of its landscapes, it presents different alternatives of use of natural resources that can take care of conservationist beginnings.